Faktor-Faktor Yang Mempengaruhi Perilaku Agresif Remaja Di Smk Negeri 2 Pekanbaru - Junia - Trisnawati; Fathra Annis Nauli; Agrina - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to determine factors associated with aggressive behavior of adolescents at vocational high school 2 Pekanbaru. The method of this study used descriptive correlative with cross sectional approach. The study was conducted in vacational high school 2 Pekanbaru with a sample 94 students. The sampling methode used was proportionate stratified random sampling. The instrument used was questionnaire that has been tested for validity and reliability. An analysis used was univariate and bivariate analisis using Chi-Square test. From the statistic data showed that there was significant relation (p value<0.05) between variables patterns of parenting (p value= 0.002), peer group (p value = 0,000) and frustration (p value = 0,006) with aggressive behavior and there was no significant relation (p value > 0.05) between electronic media (p value= 0,065) with aggressive behaviour of adolescents at vocational high school 2 Pekanbaru. This study suggested to the health institution to give health education about aggressive behavior so adolescent can take the prevention of aggressive behavior. Keyword: Adolescents, Agrressive, Behavior